French exit - Jacobs, Azazel; deWitt, Patrick, 1975-; Pfeiffer, Michelle, 1957-; Hedges, Lucas, 1996-; Letts, Tracy, 1965-; Mahaffey, Valerie; Coyne, Susan; Poots, Imogen, 1989-; deWitt, Patrick, 1975-; Sony Pictures Home Entertainment (Firm) (Culver City, CA : Sony Pictures Home Entertainment, 2021)
Sixty-year-old penniless Manhattan socialite Frances Price had a plan to die before the money ran out, but things didn't go as planned. Her husband Franklin has been dead for twelve years and with his vast inheritance gone, she cashes in the last of her possessions and resolves to live out her twilight days anonymously in a borrowed apartment in Paris. She is accompanied by her directionless son Malcolm and a cat named Small Frank, who may or may not embody the spirit of Frances's dead husband.
Originally released as a motion picture in 2021.
Based on the book by Patrick DeWitt.
Not all language options printed on container insert.
Special features: deleted & extended scenes.
Michelle Pfeiffer, Lucas Hedges, Tracy Letts, Valerie Mahaffey, Susan Coyne, Imogen Poots.
Rating: R; for language and sexual references.
Keywords: Upper class families -- Drama; Widows -- Drama; Mothers and sons -- Drama; Bankruptcy -- Drama; Video recordings for the hearing impaired; Video recordings for people with visual disabilities